Epitaxial Growth of Lead‐Free 2D Cs3Cu2I5 Perovskites for High‐Performance UV Photodetectors (Small 27/2022). Issue 27 (7th July 2022) - Lv, Jianan; Lu, Xinyue; Li, Xin; Xu, Minxuan; Zhong, Jiasong; Zheng, Xin; Shi, Yueqin; Zhang, Xuefeng; Zhang, Qi
Abstract : UV Photodetectors In article number 2201715, Qi Zhang and co‐workers propose the epitaxial growth of 2D all‐inorganic lead‐free Cs3 Cu2 I5 perovskites down to a thickness of 10 nm. The radiative transition of self‐trapped excitons is responsible for a strong blue emission, associated with a large Stocks shift and microsecond decay time. Their appealing UV sensitivity endows the development of green optoelectronic devices.